Creativity and Aesthetics of Keychain Carving At The Jati Nugroho Business Unit in Tahunan Village Jepara - rohman, fadlur; Cahyono, Agus; Wadiyo, Wadiyo (Universitas Negeri Semarang, 2021)
Keychain carving is a form of carving that is produced by the young generation at the Jati Nugroho Business Unit in Tahunan Village, Jepara. This study aims to provide an overview of the aesthetic and creative form of keychain crafts. The research was conducted using qualitative analysis research methods with the research location in the Jati Nugroho Business Unit, Tahunan Village, Jepara. The instruments and data collection techniques used observation, interviews and document studies. The data validity technique used data triangulation techniques. Meanwhile, data analysis and processing techniques were carried out by collecting, reducing, presenting and verifying data.The aesthetic form produced in the keychain craft is expected to instill values in the daily life of community. The value given is also an added value for the young generation because it has been given earlier by the family (parents) and the environment surrounds them. The value instilled in the young generation is a good effort because it makes craftsmen have knowledge, especially through the keychain carving.The data were analyzed using aesthetic form and creativity theory. The results show the following things. First, the keychain carving has a variety of shapes and aesthetic form. Second, the craftsmen have creativity in developing the latest design ideas.